Method of thermometric determination of thermophysical characteristics of thermolabs materials - Mazurenko, Olga; Kharchenko, Liliya; Kolomiets, Dmitro; Mazurenko, Alexander (My University, 2019)
To study the thermophysical characteristics of thermolabial materials, the most suitable thermometric means of their complex definition, which allow to conduct research in the presence or absence of material phase transformations of its constituents. The calorimetric measuring instruments are based on the measurement of the temperature of the heat fluxes that penetrate the sample under different thermal conditions. Thermal, electric and other transmission processes in thermometric materials determine the instability of the transformation function and form an instrumental error. On the basis of the calculation and graphic analysis of the thermal and capacitive resistance of the "device-sampler" system, a fundamentally new method has been developed, according to which the thermophysical characteristics of the material and the metrological characteristics of the device are determined in a complex and simultaneously based on the results of the experiment with samples of only the test material.
Keywords: продукти; теплообмін; характеристики; точність; метрологія; products; heat transfer; characteristics; metrology; precision; кафедра експертизи харчових продуктів; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки; кафедра електропостачання і енергоменеджменту